Modelling Social Psychological Support within the System of Inclusive Higher Education: The Experience of Novosibirsk State Technical University - Osmuk L.A; Degtyaryova V.V; Zhdanova I.V (Moscow State University of Psychology and Education, 2017)
The article considers the problem of modelling the specific structure of social psychological support of students with disabilities in the context of inclusive education development. The article reveals the functions, system character and means of application of this structure in the course of realization of professional and educational paths. The authors analyze different models of social psychological support in the university and address the question of the efficiency of these models and their compliance with resources and demands of the university. The problem of the optimal model is considered. The authors suggest outsourcing as a solution for universities with limited number of assistive resources and small amount of students with disabilities. Developing the model implies taking into account perceptions and assessments of social psychological support in students with disabilities in each step of their professional path.